PENGARUH PEMBERIAN KOMPOS LIMBAH SAYUR-SAYURAN TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Miduk Erianto Situmorang; Tengku Nurhidayah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to study the effect and to obtain the best dose of vegetables waste compost on the growth of the cocoa seedlings. The experiment has been conducted at the experimental farm of the Faculty of Agriculture, Riau University Pekanbaru from September to January 2017. The experimental unit was arranged in a Completely Randomized Design (RAL), consisting of 6 treatments: 0, 25, 50, 75, 100and 125 g/seedling and replicated 3 times. Each experimental unit consisted of 3 seedlings. Parameters observed were seedling height,stem diameter, number of leaves, leaf area, root volume, the ratio of the canopy and root and dry weight. Data were analyzed statistically using analysis of variance and the mean of each of treatment was compared with Duncan’s New Multiple Range Test at level 5 %. The result showed that the dose vegetables waste compost at 125 g/seedling produced the best growth of cocoa seedling.Keywords :cocoa seedling, vegetabless compost dose.